1998
DOI: 10.1177/089686089801800211
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Amino Acid and Protein Losses with 1.1% Amino Acid Peritoneal Dialysis Solution

Abstract: Objective Losses of nutrients into dialysate may contribute to malnutrition. Peritoneal dialysis (PD) patients are reported to lose 3 -4 g/day of amino acids (AAs) and 4 -15 g/day of proteins. The extent to which one exchange with a 1.1% AA dialysis solution (Nutrineal, Baxter, Deerfield, IL, U.s.A.) offsets these losses was investigated in a 3-day inpatient study in 20 PD patients. Design Simple, open-label, cross-over study on consecutive days in a clinical research unit. On day 1 all patients were given a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…During the exchange period of 2 L of 1.1% AAC dialysate (4-6 h), approximately 80% ($18 g) of AAs is absorbed from the peritoneal membrane. 7,22 This AAs replacement may contribute AA's recruitment in PD patients who are experiencing malnutrition. Many studies have revealed improvements in nutritional parameters, such as a significant increase in serum protein, albumin levels, nitrogen balance, BMI and recovery of plasma AAs profile after 1.1% AAC dialysate initiation in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the exchange period of 2 L of 1.1% AAC dialysate (4-6 h), approximately 80% ($18 g) of AAs is absorbed from the peritoneal membrane. 7,22 This AAs replacement may contribute AA's recruitment in PD patients who are experiencing malnutrition. Many studies have revealed improvements in nutritional parameters, such as a significant increase in serum protein, albumin levels, nitrogen balance, BMI and recovery of plasma AAs profile after 1.1% AAC dialysate initiation in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on CAPD usually loose 4 to 8 g of proteins per day and 2.0 to 2.5 g of amino acid to the peritoneal membrane 20…”
Section: Amino Acid Dialysis Fluidsmentioning
confidence: 99%
“…It has been demonstrated that the infusion of a solution containing amino acids (2 L of 1.1%) during one exchange results in an average amino acid absorption of 17.6 g/day, that is twice as large as the dialysate losses of amino acids and proteins (on average 9.2 g/day) 20. Treatment with intraperitoneal amino acid solution results in a positive nitrogen balance, a significant increase in net protein anabolism, and more normal fasting plasma amino acid pattern, and significant increases in serum total protein and transferring 21.…”
Section: Amino Acid Dialysis Fluidsmentioning
confidence: 99%
“…[17][18][19] Likewise, peritoneal dialysis patients can lose 5-15 g of protein per day. 20 Because of the severe restrictions imposed by the renal diet, including fruits, vegetables, dairy, and fluids, patient compliance with the diet can also lead to challenges. When oral liquid supplements are used in an effort to increase oral nutrient intake, taste fatigue can develop, reducing patient acceptance and consumption.…”
Section: Malnutrition In Chronic Kidney Diseasementioning
confidence: 99%